THE BENEFITS AND CHALLENGES OF TELEMEDICINE IN EMERGENCY MEDICINE - Saleh Turki Hamad Alothman, Salman Saleh Alshamsan,, Mohamed Suluiman Mohamed Alkataf, Mousa Muflih Atqaa Rashdi, Rayan Abdulaziz Ali Alkhamis,,; Fahad Hussain Jufain Almutairi, Abdullah Awadh Almutairi, Ibrahim Awadh Almutairi, Essa Abdu Allah Mohammed, (Chelonian Research Foundation, 2022)
The utilization of telemedicine in the emergency department (ED) is supported by both positive and negative evidence, which has generated doubt regarding the efficacy of these systems. We conducted a comprehensive literature review on systematic reviews in order to present a synopsis of the advantages and obstacles associated with the implementation of telemedicine systems in the emergency department.Systematic evaluations of telemedicine applications for the emergency department were discovered in the PubMed, Web of Science, Scopus, Cochrane Library, and Google Scholar databases. Before data items were extracted and evaluated, each review was evaluated critically by two authors. A study was conducted and reported on the most highly suggested technologies, practicality, advantages, and obstacles associated with the implementation of telemedicine systems.The main findings of eighteen investigations with different methodological quality were summarized. Twelve of the eighteen studies included in this collection exhibited a significant degree of bias in their research. Real-time video conferencing was identified as the most effective delivery method in nine of the papers, resulting in cost savings for eight of the papers that examined the subject. However, technical and infrastructure challenges arose in six of the studies that examined the implementation of telemedicine for emergency departments.Robust evidence exists to support the notion that telemedicine has a beneficial effect on the provision of patient treatment. Nonetheless, the implementation of telemedicine faces numerous obstacles that have the potential to hinder progress and compromise patient safety. In conclusion, notwithstanding the considerable potential of telemedicine systems, more robust evidence is required to validate their viability within the emergency department